Integrality gap minimization heuristics for binary mixed integer nonlinear programming - Melo, Wendel; Fampa, Marcia; Raupp, Fernanda (Journal of global optimization, 2018)
We present two feasibility heuristics for binary mixed integer nonlinear programming. Called integrality gap minimization algorithm (IGMA)—versions 1 and 2, our heuristics are based on the solution of integrality gap minimization problems with a space partitioning scheme defined over the integer variables of the problem addressed. Computational results on a set of benchmark instances show that the proposed approaches present satisfactory results.